Effect of the interaction between childhood abuse and rs1360780 of the FKBP5 gene on gray matter volume in a general population sample - Grabe, Hans Jörgen (Hum Brain Mapp, 2016)
OBJECTIVE: The FKBP5 gene codes for a co‐chaperone that regulates glucocorticoid receptor sensitivity and thereby impacts the reactivity of the hypothalamic–pituitary–adrenal (HPA)‐axis. Evidence suggested that subjects exposed to childhood abuse and carrying the TT genotype of the FKBP5 gene single nucleotide polymorphism (SNP) rs1360780 have an increased susceptibility to stress‐related disorders. METHOD: The hypothesis that abused TT genotype carriers show changes in gray matter (GM) volumes in affect‐processing brain areas was investigated. About 1,826 Caucasian subjects (age ≤ 65 years) from the general population [Study of Health in Pomerania (SHIP)] in Germany were investigated. The interaction between rs1360780 and child abuse (Childhood Trauma Questionnaire) and its effect on GM were analyzed. RESULTS: Voxel‐based whole‐brain interaction analysis revealed three large clusters (FWE‐corrected) of reduced GM volumes comprising the bilateral insula, the superior and middle temporal gyrus, the bilateral hippocampus, the right amygdala, and the bilateral anterior cingulate cortex in abused TT carriers. These results were not confounded by major depressive disorders. In region of interest analyses, highly significant volume reductions in the right hippocampus/parahippocampus, the bilateral anterior and middle cingulate cortex, the insula, and the amygdala were confirmed in abused TT carriers compared with abused CT/CC carriers. CONCLUSION: The results supported the hypothesis that the FKBP5 rs1360780 TT genotype predisposes subjects who have experienced childhood abuse to widespread structural brain changes in the subcortical and cortical emotion‐processing brain areas. Those brain changes might contribute to an increased vulnerability of stress‐related disorders in TT genotype carriers. Hum Brain Mapp 37:1602‐1613, 2016. © 2016 Wiley Periodicals, Inc.